Effects of non-invasive brain stimulation in dystonia: a systematic review and meta-analysis. (December 2022) - Morrison-Ham, Jordan; Clark, Gillian M.; Ellis, Elizabeth G.; Cerins, Andris; Joutsa, Juho; Enticott, Peter G.; Corp, Daniel T.
Background: Deep brain stimulation is a highly effective treatment of dystonia but is invasive and associated with risks, such as intraoperative bleeding and infections. Previous research has used non-invasive brain stimulation (NIBS) in an attempt to alleviate symptoms of dystonia. The results of these studies, however, have been variable, leaving efficacy unclear. Objectives: This study aimed to evaluate the effects of NIBS on symptoms of dystonia and determine whether methodological characteristics are associated with variability in effect size. Methods: Web of Science, Embase, and MEDLINE Complete databases were searched for articles using any type of NIBS as an intervention in dystonia patients, with changes in dystonia symptoms the primary outcome of interest. Results: Meta-analysis of 27 studies demonstrated a small effect size for NIBS in reducing symptoms of dystonia (random-effects Hedges' g  = 0.21, p  = .002). Differences in the type of NIBS, type of dystonia, and brain region stimulated had a significant effect on dystonia symptoms. Meta-regression revealed that 10 sessions of active stimulation and the application of concurrent motor training programs resulted in significantly larger mean effect sizes. Conclusion: NIBS has yielded small improvements to dystonic symptoms, but effect sizes depended on methodological characteristics, with more sessions of stimulation producing a larger response. Future research should further investigate the application of NIBS parallel to motor training, in addition to providing a greater quantity of sessions, to help define optimal parameters for NIBS protocols in dystonia. Registration: PROSPERO 2020, CRD42020175944.